[99mTc]Tc-iFAP/SPECT Tumor Stroma Imaging: Acquisition and Analysis of Clinical Images in Six Different Cancer Entities - Paola Vallejo-Armenta; Guillermina Ferro-Flores; Clara Santos-Cuevas; Francisco Osvaldo García-Pérez; Pamela Casanova-Triviño; Bayron Sandoval-Bonilla; Blanca Ocampo-García; Erika Azorín-Vega; Myrna Luna-Gutiérrez (MDPI AG, 2022)
Fibroblast activation protein (FAP) is highly expressed on the cancer-associated fibroblasts (CAF) of the tumor stroma. Recently, we reported the preclinical evaluation and clinical biokinetics of a novel 99mTc-labeled FAP inhibitor radioligand ([99mTc]Tc-iFAP). This research aimed to evaluate [99mTc]Tc-iFAP for the tumor stroma imaging of six different cancerous entities and analyze them from the perspective of stromal heterogeneity. [99mTc]Tc-iFAP was prepared from freeze-dried kits with a radiochemical purity of 98 ± 1%. The study included thirty-two patients diagnosed with glioma (n = 5); adrenal cortex neuroendocrine tumor (n = 1); and breast (n = 21), lung (n = 2), colorectal (n = 1) and cervical (n = 3) cancer. Patients with glioma had been evaluated with a previous cranial MRI scan and the rest of the patients had been involved in a [18F]FDG PET/CT study. All oncological diagnoses were corroborated histopathologically. The patients underwent SPECT/CT brain imaging (glioma) or thoracoabdominal imaging 1 h after [99mTc]Tc-iFAP administration (i.v., 735 ± 63 MBq). The total lesions (n = 111) were divided into three categories: primary tumors (PT), lymph node metastases (LNm), and distant metastases (Dm). [99mTc]Tc-iFAP brain imaging was positive in four high-grade WHO III-IV gliomas and negative in one treatment-naive low-grade glioma. Both [99mTc]Tc-iFAP and [18F]FDG detected 26 (100%) PT, although the number of positive LNm and Dm was significantly higher with [18F]FDG [82 (96%)], in comparison to [99mTc]Tc-iFAP imaging (35 (41%)). Peritoneal carcinomatosis lesions in a patient with recurrent colorectal cancer were only visualized with [99mTc]Tc-iFAP. In patients with breast cancer, a significant positive correlation was demonstrated among [99mTc]Tc-iFAP uptake values (Bq/cm3) of PT and the molecular subtype, being higher for subtypes HER2+ and Luminal B HER2-enriched. Four different CAF subpopulations have previously been described for LNm of breast cancer (from CAF-S1 to CAF-S4). The only subpopulation that expresses FAP is CAF-S1, which is preferentially detected in aggressive subtypes (HER2 and triple-negative), confirming that FAP+ is a marker for poor disease prognosis. The results of this pilot clinical research show that [99mTc]Tc-iFAP SPECT imaging is a promising tool in the prognostic assessment of some solid tumors, particularly breast cancer.